Basis of serviceability limit state target reliability: Fact or fiction? - Viljoen, Celeste; ICASP14; McLeod, Christina; Way, Andrew (My University, 2023)
Target reliability forms the basis of modern structural design and finds its root in cost optimisation. Ultimate limit state (ULS) target reliability is well-founded and has been extensively researched. Serviceability limit state (SLS) target reliability, however, has received comparatively little attention and its basis is obscure. This is concerning, given that SLS criteria governs the design of some structural members and sometimes entire structures, as is the case for water retaining structures. The widely accepted, lifetime reversible and irreversible SLS target reliabilities of 0 and 1.5, respectively, are said to be a result of generic cost optimisation. However, the SLS consequences of failure (CoF) and costs of increasing safety (CoS) assumed in the generic cost optimisation are at best qualitatively defined in existing literature, which begs the question: What really forms the basis of SLS target reliability? This research aims to investigate the basis of generic SLS target reliability in concrete structures from a cost optimisation perspective, across a range of CoF and CoS values. Practical reversible and irreversible SLS example cases with representative CoF and CoS are considered, and the results of the generic cost optimisation are compared to those from the specific example cases. The results are used to comment on the appropriateness of SLS target reliability. Where it may be found to be inappropriate, more fitting values are suggested, based on the CoF and CoS ranges that are appropriate to them.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED